Calcium aluminate–diatomaceous earth composite as a reactive filter material for aqua defluoridation. (February 2016) - Oladoja, N.A.; Helmreich, B.
Abstract: Calcium aluminate (CA) was prepared through a self-propagation combustion method and got incorporated, in-situ, into the framework of diatomaceous earth (DE) to produce a composite material (CA–DE) that is capable of serving as a reactive filter material for groundwater defluoridation. Aqua defluoridation potential of the CA–DE was evaluated and optimized in a batch process. The XRD analysis of the CA–DE showed that amorphous CA was incorporated into the DE. The results of the kinetic analysis of the defluoridation process showed that the time-concentration profiles, at different initial F − concentrations, were best described by the pseudo-second order kinetic equation. The appraisal of the performance efficiency of the CA–DE, via equilibrium isotherm analysis showed that the monolayer sorption capacity of the CA–DE was 18.22 mg/g and Freundlich isotherm equation gave better description of the defluoridation process. Variation in ionic strength, pH, anionic interference, organic load had minimal effects on the extent of aqua defluoridation by the CA–DE.